2004
DOI: 10.1107/s0909049504024835
|View full text |Cite
|
Sign up to set email alerts
|

Suite of three protein crystallography beamlines with single superconducting bend magnet as the source

Abstract: SynopsisThree near identical protein crystallography beamlines with a single 6 Tesla peak field superconducting dipole bend magnet as the source have been built at the 1.9 GeV Advanced Light Source. The design and performance of this new facility is described. AbstractAt the Advanced Light Source (ALS), three protein crystallography (PX) beamlines have been built that use as a source one of the three 6 Tesla single pole superconducting bending magnets (superbends) that were recently installed in the ring. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 7 publications
1
81
0
Order By: Relevance
“…The change in focus location is achieved by slight change of the M2 tilt angle. Previously [1] we found that when the toroidal mirror is used with parallel illumination in the vertical and a 2:1 demagnification in the horizontal, then the main aberrations cancel out and a high quality image results. This has been determined to be due to the vanishing of the astigmatic coma for the 2:1 horizontal demagnification case [5].…”
Section: Source Beamline and End-station Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The change in focus location is achieved by slight change of the M2 tilt angle. Previously [1] we found that when the toroidal mirror is used with parallel illumination in the vertical and a 2:1 demagnification in the horizontal, then the main aberrations cancel out and a high quality image results. This has been determined to be due to the vanishing of the astigmatic coma for the 2:1 horizontal demagnification case [5].…”
Section: Source Beamline and End-station Descriptionmentioning
confidence: 99%
“…The basic beamline layout was the same employed on the previous PX superbend beamlines [1]. The beamline design adopted is shown schematically in Fig.1.…”
Section: Source Beamline and End-station Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diffraction data were collected at the Lawrence Berkeley National Laboratory Advanced Light Source Beamline 8.3.1. 21 Data were scaled using HKL2000. The PHENIX software suite 22 was used for model building by molecular replacement using the RpfB homolog (3EO5 in PDB) as the search model.…”
Section: Rpfe Crystallization Data Collection and Structure Determinmentioning
confidence: 99%